Hepatitis B virus-infection related cryoglobulinemic vasculitis. Clinical manifestations and the effect of antiviral therapy: A review of the literature - Mazzaro, Cesare; Bomben, Riccardo; Visentini, Marcella; Gragnani, Laura; Quartuccio, Luca; Saccardo, Francesco; Sebastiani, Marco; Filippini, Davide; Lauletta, Gianfranco; Monti, Giuseppe; Gattei, Valter (Frontiers in Oncology, 2023)
Objective Hepatitis B virus (HBV) infection causes chronic hepatitis, cirrhosis, and hepatocellular carcinoma. Furthermore, about 20% of the patients develop extrahepatic manifestations such as cryoglobulinemic vasculitis (CV), polyarteritis nodosa, non-rheumatoid arthritis, glomerulonephritis and non-Hodgkin lymphoma. This review analyzed literature data on clinical manifestations of HBV-related CV and the impact of antiviral therapy with analoques nucleotide. Methods A PubMed search was performed to select eligible studies in the literature, up to July 2022. Results Some studies have analyzed clinical manifestations in HBV-related CV and have investigated the role of antiviral therapy with nucleotides analogues (NAs). Clinical manifestations of CV vary from mild to moderate (purpura, asthenia and arthralgias) to severe (leg ulcers, peripheral neuropathy, glomerulonephritis, and non-Hodking lymphoma). NAs therapy leads to suppression of HBV-DNA; therefore, it is capable of producing clinical response in the majority of patients with mild to moderate symptoms. Conclusion Antiviral therapy with NAs is the first choice for HBV suppression and control of mild to moderate disease. In severe vasculitis (glomerulonephritis, progressive peripheral neuropathy and leg ulcers), rituximab alone or with plasma-exchange is always indicated in combination with antiviral therapy.